Cambio y continuidad en el debate sobre la dependencia y el imperialismo - Muñoz, Heraldo (Estudios Internacionales, 1978)
This work has two objectives: first, to analyze and clarify the development and the main focus of discussion of what has come to be called "dependency theory" and, second, to introduce new concepts and analysis topics within this same theoretical framework, especially considering the various changes that the world political economy has undergone before and after the oil crisis. For this, first a descriptive-historical analysis of the emergence and development of the theoretical perspective of dependency in Latin America is included; then a critical examination of key issues and / or problems that have been the focus of the discussion on dependency and imperialism is carried out and, finally, the concept of strategic dependency is introduced.